2017
DOI: 10.1371/journal.pone.0184259
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with AFLP genotyping errors to reveal genetic structure in Plukenetia volubilis (Euphorbiaceae) in the Peruvian Amazon

Abstract: An analysis of the population structure and genetic diversity for any organism often depends on one or more molecular marker techniques. Nonetheless, these techniques are not absolutely reliable because of various sources of errors arising during the genotyping process. Thus, a complex analysis of genotyping error was carried out with the AFLP method in 169 samples of the oil seed plant Plukenetia volubilis L. from small isolated subpopulations in the Peruvian Amazon. Samples were collected in nine localities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…Most studies of genotyping error in dominant markers have been carried out on AFLP data. Vašek et al (2017), in a recent study, found that error rate affected descriptive parameters of diversity such as H e , %P and Φ PT more strongly than the results of Bayesian STRU CTU RE analysis. We therefore judge that our observed genotyping error (6.7%, which compares to the 5% maximum AFLP error rate used by Vašek et al 2017) is unlikely to have affected the optimal 8-group genetic structure or the relative values of the genetic diversity parameters among the wild and domesticated populations.…”
Section: Discussionmentioning
confidence: 91%
“…Most studies of genotyping error in dominant markers have been carried out on AFLP data. Vašek et al (2017), in a recent study, found that error rate affected descriptive parameters of diversity such as H e , %P and Φ PT more strongly than the results of Bayesian STRU CTU RE analysis. We therefore judge that our observed genotyping error (6.7%, which compares to the 5% maximum AFLP error rate used by Vašek et al 2017) is unlikely to have affected the optimal 8-group genetic structure or the relative values of the genetic diversity parameters among the wild and domesticated populations.…”
Section: Discussionmentioning
confidence: 91%
“…In general, AFLP markers revealed a high degree of polymorphism and proved to be a useful and reliable tool for characterizing genetic diversity in sacha inchi progenies, as also reported by Vašek et al (2017). In addition, AFLP markers were highly informative in evaluating the reproductive system of sacha inchi.…”
Section: Resultsmentioning
confidence: 56%
“…AFLP analysis can incorporate hundreds of polymorphisms across a whole genome, but it suffers from relatively high genotyping error (Zhang and Hare 2012) that can significantly affect analysis of population structure and make it impossible to determine the 'true' number of populations among a set of individuals. Mensch (2009) reports shifting AFLP peak profiles between individuals included in her study, which may have resulted in incorrect genotyping and thus the greater number of genetic lineages detected (Vašek et al 2017). It is not clear if the lineages described here coincide with any of those identified by Mensch (2009) with the genetic data from that study unavailable, but the weight of genetic evidence suggests the existence of (at least) two morphologically cryptic but reproductively isolated species within S. nitida.…”
Section: Discussionmentioning
confidence: 74%